2016
DOI: 10.3168/jds.2015-9908
|View full text |Cite
|
Sign up to set email alerts
|

Dry period plane of energy: Effects on glucose tolerance in transition dairy cows

Abstract: Overfeeding energy in the dry period can affect glucose metabolism and the energy balance of transition dairy cows with potential detrimental effects on the ability to successfully adapt to early lactation. The objectives of this study were to investigate the effect of different dry cow feeding strategies on glucose tolerance and on resting concentrations of blood glucose, glucagon, insulin, nonesterified fatty acids (NEFA), and β-hydroxybutyrate (BHB) in the peripartum period. Cows entering second or greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
61
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 57 publications
15
61
3
2
Order By: Relevance
“…() and Sano et al. () found a lower insulin response to glucose infusion in lactating cows compared with non‐lactating animals, which indicates the necessity of maintenance of nutrient direction towards the mammary gland during lactation (Mann et al., ). Furthermore, Thompson, Weiser, Seto, and Black () and Lomax, Baird, Symonds, Mallinson, and Shaw () reported a decreased hepatic glucose production and reduced uptake of gluconeogenic precursors in cows following glucose infusion.…”
Section: Discussionmentioning
confidence: 99%
“…() and Sano et al. () found a lower insulin response to glucose infusion in lactating cows compared with non‐lactating animals, which indicates the necessity of maintenance of nutrient direction towards the mammary gland during lactation (Mann et al., ). Furthermore, Thompson, Weiser, Seto, and Black () and Lomax, Baird, Symonds, Mallinson, and Shaw () reported a decreased hepatic glucose production and reduced uptake of gluconeogenic precursors in cows following glucose infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Two important metabolic adaptations that facilitate glucose partitioning toward the fetus and the mammary gland include a progressive reduction of insulin secretion by the pancreas, and impaired insulin responsiveness in adipose and skeletal muscle tissues [4, 5]. The progressive development of insulin resistance during peripartum has been validated through direct measurements of insulin secretion and responsiveness, such as glucose tolerance testing and insulin tolerance testing [6, 7, 8]. Because insulin is an anti-lipolytic hormone, the excessive mobilization of fatty acids from adipose tissue is an unfavorable outcome of reduced insulin action.…”
Section: Introductionmentioning
confidence: 99%
“…Cows with postpartum ketosis have lower circulating concentrations of glucose than herdmates (Mann and others 2016b). More recently, we showed that intravenous glucose administration (Fig 2) in addition to oral propylene glycol was able to lower BHB concentrations to a greater extent and duration in hyperketonaemic postpartum cows (Mann and others 2017).…”
Section: Ketosismentioning
confidence: 99%